Genetic loci of hemolysin production in Streptococcus faecalis subsp. zymogenes. - Frazier, M L (1977)
Two plasmids corresponding to molecular weights of 38.5 X 10(6) and 3.6 X 10(6) have been identified in Streptococcus faecalis subsp. zymogenes strain X-14. The larger plasmid is required for hemolysin-bacteriolysin production. Strain L2, a nonlytic nitrosoquanidine mutant of strain X-14, still harbors the hemolytic plasmid and produces the lysin component, but not the activator component, of the lytic system. Conjugal transfer of this plasmid from strain L2 to plasmid-free strains and strains cured of the 38.5-megadalton plasmid gives rise to hemolytic recipients. This implicates a gene in hemolysin production at a site other than the 38.5-megadalton plasmid.